QADIMGI BAQTRIYA DAVLATIDA IJTIMOIY-IQTISODIY HAYOT - Toshtemirov Abduvalixon Abdivohid og’li, Ostanaqulov Azizbek Samijon o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article mainly provides information about the formation, borders and socio-economic life of the ancient Bactrian state. In addition, information about the ancient Bactrian state, provided by ancient Greek scholars and Avesta sources, military campaigns carried out by this state, as well as the politics and cultural life of the Bactrian state during the Achaemenid dynasty, is given.